Maternal Cardiac Assessment at 35 to 37 Weeks Improves Prediction of Development of Preeclampsia. Issue 2 (August 2020) - Garcia-Gonzalez, Coral; Georgiopoulos, Georgios; Azim, Samira Abdel; Macaya, Fernando; Kametas, Nikos; Nihoyannopoulos, Petros; Nicolaides, Kypros H.; Charakida, Marietta
Abstract : Preeclampsia at term accounts for half of maternal deaths from hypertensive disorders. We aimed to assess differences in maternal cardiac indices at 35 +0 to 36 +6 weeks' gestation between women who subsequently developed preeclampsia at term compared with those with uncomplicated pregnancy and to evaluate whether cardiac indices offer incremental prognostic value to the available screening algorithm for preeclampsia. We recruited 1602 women with singleton pregnancies who attended for a routine hospital visit at 35 +0 to 36 +6 weeks' gestation between April and November 2018. We recorded maternal characteristics and preeclampsia-risk-score derived from a competing risks model and measured cardiac indices. Preeclampsia developed in 3.12% (50/1602) of participants. Women with preeclampsia, compared with those without, had increased mean arterial pressure (97.6, SD, 5.53 versus 87.9, SD, 6.82 mm Hg), systemic vascular resistance (1500, interquartile range, 1393–1831 versus 1400, interquartile range, 1202–1630 PRU) and preeclampsia-risk-score (23.4, interquartile range, 9.13–40 versus 0.9, interquartile range, 0.32–3.25). Multivariable analysis demonstrated independent association between the incidence of preeclampsia and E/e′ (hazard ratio, 1.19/unit [95% CI, 1.03–1.37]; P =0.018) as well as left ventricular mass indexed for body surface area (hazard ratio, 1.03/[g·m 2 ] [95% CI, 1.003–1.051]; P =0.029). Women with E/e′ ≥7.3 and left ventricular mass indexed for body surface area ≥63.2 g/m 2 had an increased risk for developing preeclampsia, despite low preeclampsia-risk-score <5% (hazard ratio, 20.1 [95% CI, 10.5–38.7], P <0.001). Increased left ventricular mass and E/e′ offer incremental information to available scoring systems and better stratify women at risk of developing preeclampsia at term. Abstract : Supplemental Digital Content is available in the text.